2007
DOI: 10.1177/0269216307080823
|View full text |Cite
|
Sign up to set email alerts
|

Truth-telling in discussing prognosis in advanced life-limiting illnesses: a systematic review

Abstract: Many health professionals (HPs) express discomfort at having to broach the topic of prognosis, including limited life expectancy, and may withhold information or not disclose prognosis. A systematic review was conducted of 46 studies relating to truth-telling in discussing prognosis with patients with progressive, advanced life-limiting illnesses and their caregivers. Relevant studies meeting the inclusion criteria were identified by searching computerized databases (MEDLINE, EMBASE, CINAHL, PsychINFO and Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
326
2
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 367 publications
(351 citation statements)
references
References 58 publications
5
326
2
10
Order By: Relevance
“…There is evidence that many professionals lack confidence in undertaking ACP and tend to avoid such discussions. 13,14,35,53,67,87,88 Several studies suggest that, as there is uncertainty about which professional should undertake discussion of ACP, there is a tendency, particularly among GPs, to defer responsibility to someone else. 9,12,53,64,67,89 Evidence also suggests that, although patients tend to expect professionals to take the initiative, there is a tendency for professionals to wait for patients to open the discussion.…”
Section: Preferred Place Of Deathmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that many professionals lack confidence in undertaking ACP and tend to avoid such discussions. 13,14,35,53,67,87,88 Several studies suggest that, as there is uncertainty about which professional should undertake discussion of ACP, there is a tendency, particularly among GPs, to defer responsibility to someone else. 9,12,53,64,67,89 Evidence also suggests that, although patients tend to expect professionals to take the initiative, there is a tendency for professionals to wait for patients to open the discussion.…”
Section: Preferred Place Of Deathmentioning
confidence: 99%
“…4 However, it is apparent that ACP remains uncommon in most areas of professional practice and that both professionals and patients tend to avoid discussions they find difficult. [5][6][7][8][9][10][11][12][13][14] Patient and family responses to ACP and its effect on EOLC outcomes remain poorly understood. This study contributes to the currently limited evidence relating to the nature and impact of ACP as well as a critical appraisal of its contribution within current EOLC policy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Nonetheless, some physicians might not tell patients the full truth, to avoid upsetting them or causing them to lose hope. 22,[42][43][44] Especially in the context of lifethreatening illness, physicians might not tell patients the complete truth because of lack of training, time limitations, uncertainty about prognostic accuracy, family requests, and feelings of inadequacy about their medical interventions. 44 Physicians' sex and race or ethnicity were significantly associated with fewer than half of the communication areas we assessed (four of the nine questions for sex and two for race or ethnicity).…”
mentioning
confidence: 99%
“…22,[42][43][44] Especially in the context of lifethreatening illness, physicians might not tell patients the complete truth because of lack of training, time limitations, uncertainty about prognostic accuracy, family requests, and feelings of inadequacy about their medical interventions. 44 Physicians' sex and race or ethnicity were significantly associated with fewer than half of the communication areas we assessed (four of the nine questions for sex and two for race or ethnicity). However, in all six instances, the direction of the differences suggested that women were more likely than men, and underrepresented minorities were more likely than whites or Asians, to follow charter principles.…”
mentioning
confidence: 99%